SEDIMENTATION AND DEPOSITIONAL ENVIRONMENT BASED ON SEISMIC AND DRILLING CORE ANALYSES IN CIMANUK DELTA INDRAMAYU, WEST JAVA - I Nyoman Astawa (BULLETIN OF THE MARINE GEOLOGY, 2009)
Core drilling had been carried out in three locations such as in Brondong Village (BH-01), Pasekan Village (BH-02), and Karangsong Village (BH-03). Those three cores are similar in lithology consist of clay. They are correlated based on fragment content, such as fine sand lenses, mollusk shells, rock and carbonate materials which discovered from different depths. Single side band of shallow seismic reflection recorded paleochannels in E sequence at the north and the west of investigated area. It’s predicted the north paleo channels were part of Lawas River or Tegar River, while the west paleo channels were part of Rambatan Lama River. Microfauna content of all those three cores indicated that from the depth of 0.00 meter down to 25,00 meters are Holocene/Recent, from 25,00 meters to the bottom are Pleistocene which were deposited in the bay to middle neritic environment. Key words: Core drilling, seismic interpretation, Cimanuk Delta Pemboran inti dilakukan di 3 (tiga) lokasi yaitu di Desa Brondong (BH-01), Desa Pasekan (BH- 02), dan Desa Karangsong (BH-03). Ke tiga inti bor itu mempunyai kesamaan litologi yaitu lempung. Korelasi dilakukan berdasarkan kandungan fragmen seperti lensa-lensa pasir halus, cangkang moluska, material batuan dan material karbonat yang terdapat pada kedalaman yang berbeda. Seismik pantul dangkal saluran tunggal merekam adanya alur purba pada runtunan E di bagian utara dan barat daerah penelitian. Diduga alur purba di bagian utara merupakan bagian dari tubuh Kali Lawas atau Kali Tegar, sedangkan di bagian barat sebagai bagian dari tubuh Kali Rambatan Lama. Kandungan mikrofaunanya menunjukkan ketiga bor inti mulai kedalaman 0,00 meter sampai 25,00 meter berumur Holosen/Resen, sedangkan dari 25,00 meter sampai batas bawah pemboran berumur Plistosen yang diendapkan pada lingkungan teluk hingga Neritik Tengah. Kata kunci: Bor inti, penafsiran seismik, Delta Cimanuk.